Analysis of the Potential for Organic and Inorganic Waste Reduction at PT Asmin Bara Bronang: Analisis Potensi Reduksi Sampah Organik dan Anorganik di PT Asmin Bara Bronang - Ashfa Nadia Syahidah; Gina Lova Sari; Kania Ratnawati (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Waste management in the industrial sector presents a serious challenge that requires effective and sustainable strategies. This study aims to analyze the waste generation, composition, as well as the potential and effectiveness of waste reduction activities at PT Asmin Bara Bronang. Data were collected based on the Indonesian National Standard (SNI) 19-3964-1994 as a reference for measuring waste generation and composition. The measurements showed an average waste generation of 263.67 kg/day, with the dominant components being food waste (44.02%), paper (14.55%), and plastic (12.04%). Waste reduction efforts carried out include the cultivation of Black Soldier Fly (BSF) larvae and the processing of plastic into paving blocks and plastic sheets. However, the current effectiveness is still low, reaching only 6.75%. Through optimization analysis, food waste reduction has the potential to increase to 35.80%, and plastic waste reduction to 17.07%. Therefore, the total potential waste reduction after optimization could increase to 52.87% of the total daily waste generation.